Wavelet analysis of a flexible filament kinematics: emulating C. elegans swimming behavior - Malvar, Sara; Souza Carmo, Bruno (Journal of The Brazilian Society of Mechanical Sciences and Engineering, 2021)
This paper discusses different aspects of an active flexible filament propulsion in a liquid medium. The immersed boundary method is used to model a flexible filament immersed in Newtonian fluid at low Reynolds numbers. The flexible filament motion emulates that of a C. elegans. We varied some parameters of the filament motion, such as the interpolation points of the function related to the curvature of the filament and the upstroke and downstroke period, and analyzed the kinematic response in the body displacement and fluid flow. A methodology based on signal analysis is proposed for correct modeling of the movement of these filaments. The swimming velocity and distance are analyzed using wavelet transform, in which the notion of time–frequency localization is made precise. This methodology allows defining which parameters lead to the best efficiency, e.g., greater swim distance for the same number of strokes, making it very valuable for passive control of the filament.